Laskar Muda Organizational Management of Wayang Orang Ngesti Pandawa Performance in Semarang - Bisri, Moh. Hasan (Universitas Negeri Semarang, 2024)
Organizational management is formed to achieve common goals. Management is necessary in the artistic journey process. Laskar Muda is a forum for young people who are members of Ngesti Pandawa, the activities of Laskar Muda in Ngesti Pandawa are in the field of and become the wheels of Wayang Orang Ngesti Pandawa activities. The research aims to analyze how the Laskar Muda organization is managed and the obstacles that exist in the Ngesti Pandawa puppet show. The research method used is a qualitative method with a phenomenological approach. A phenomenological approach was used by researchers to observe phenomena related to the Management of the Young Warriors Organization in the Semarang Ngesti Pandawa Orang Puppet Performance. Data collection techniques use observation, interviews, and documentation techniques. Data validity techniques use data reduction, data presentation, and conclusions. The results of the research show that the management of the organization formed and supported by the Ngesti Pandawa leadership is mutually cooperative which can help the development of the wayang arts of the Ngesti Pandawa people. Work programs that support the pandemic era are still running even though conditions are difficult. Suggestions for the Laskar Muda organization are that organizational management is formed in a definite manner so that, in the process of managing mutual understanding, it is recommended that the Laskar Muda work program be more formatted in a regular period. Systematic management of the organization will run smoothly. The hope is that Laskar Muda will always be active in the Ngesti Pandawa organization.